OILADAGI NIZOLAR, AJRALISH VA ULARNING OLDINI OLISH YO‘LLARI - Ro‘ziqulov, F.R. (SCIENCE and SOCIETY, 2024)
In this article, the problem of family disputes and divorce is one of the most important social problems of modern human society, the causes of conflicts between husband and wife, the changing values in family relations, the unpreparedness of young people for family life, and the increase of family disputes. , recommendations are given to prevent the causes of disparity in the family roles of spouses and the ideas of the older generation and the younger generation about the family.